2023
DOI: 10.1590/1983-40632023v5374090
|View full text |Cite
|
Sign up to set email alerts
|

Physiological quality of Physalis ixocarpa Brot. ex Hornem seeds in relation to maturation stage and growing season

Abstract: Physalis ixocarpa is an edible fruit with great economic importance in many countries. The use of high-quality seeds is essential for the success of the crop, so their harvest should be carried out at their maximum point of physiological maturity. This study aimed to verify the influence of the growing season and fruit maturation stage on the seed physiological maturity of two P. ixocarpa varieties (‘green’ and ‘purple’) grown in the Brazilian semi-arid region. The water content, dry weight, germination percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Nunes et al [21] found a temperature of up to 32 • C suitable for germination of P. peruviana seeds. Ozaslan et al [47] achieved germination percentages of P. angulata and P. philadelphica seeds close to 100% at a temperature of 35 • C. For some species in the genus, a constant temperature of 25 • C was sufficient to promote high germination of P. ixocarpa L. [49], while an average temperature of 25 • C (alternating between 20 and 30 • C) was adequate to promote high germination of P. angulata L. [50]. These results indicate that each species has a temperature spectrum within which the seed can germinate.…”
Section: Experiments I: Effect Of Temperatures On Seed Germination An...mentioning
confidence: 98%
“…Nunes et al [21] found a temperature of up to 32 • C suitable for germination of P. peruviana seeds. Ozaslan et al [47] achieved germination percentages of P. angulata and P. philadelphica seeds close to 100% at a temperature of 35 • C. For some species in the genus, a constant temperature of 25 • C was sufficient to promote high germination of P. ixocarpa L. [49], while an average temperature of 25 • C (alternating between 20 and 30 • C) was adequate to promote high germination of P. angulata L. [50]. These results indicate that each species has a temperature spectrum within which the seed can germinate.…”
Section: Experiments I: Effect Of Temperatures On Seed Germination An...mentioning
confidence: 98%